2018
DOI: 10.1038/s41598-018-32818-z
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of data from spaceflight transcriptome experiments does not support the idea of a common bacterial “spaceflight response”

Abstract: Several studies have been undertaken with the goal of understanding how bacterial transcriptomes respond to the human spaceflight environment. However, these experiments have been conducted using a variety of organisms, media, culture conditions, and spaceflight hardware, and to date no cross-experiment analyses have been performed to uncover possible commonalities in their responses. In this study, eight bacterial transcriptome datasets deposited in NASA’s GeneLab Data System were standardized through a commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
(53 reference statements)
2
7
0
Order By: Relevance
“…The results obtained for Staphylococcus mutans, Escherichia coli, Mycobacterium marinum, and Streptomyces coelicolor under these conditions have been proved to be consistent with those found on the ISS (18)(19)(20)(21)(22). However, inconsistent results were also found in several studies when different bacteria, experimental setups, and cultivation conditions were used (23). The final phenotype that a bacterium exhibits is the result of its physiological response to the spaceflight environment (23).…”
supporting
confidence: 58%
See 2 more Smart Citations
“…The results obtained for Staphylococcus mutans, Escherichia coli, Mycobacterium marinum, and Streptomyces coelicolor under these conditions have been proved to be consistent with those found on the ISS (18)(19)(20)(21)(22). However, inconsistent results were also found in several studies when different bacteria, experimental setups, and cultivation conditions were used (23). The final phenotype that a bacterium exhibits is the result of its physiological response to the spaceflight environment (23).…”
supporting
confidence: 58%
“…(22,32). Although microgravity has been studied for more than 50 years, systematic and comprehensive studies of the genetic and phenotypic responses of microorganisms to the microgravity environment in space are still lacking due to inconsistencies in the experimental designs, experimental setups, and cultivation conditions used in different studies (22,23). In particular, knowledge about the impact of microgravity on the metabolism of fungi, particularly molds with a high corrosive ability, has still been very limited, until now.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the space environment altered the transcript levels of some genes in bacteria (Morrison & Nicholson, ). In this study, transcriptomic and proteomic analyses revealed that the differentially expressed genes and proteins were primarily located in pathways including flagella assembly, two‐component system, bacterial chemotaxis, and bacterial secretion system according to KEGG pathway functions.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent work mapping transcriptomic responses of S. enterica and Pseudomonas aeruginosa to spaceflight and clinorotation identified the molecular chaperone and global regulator Hfq as being implicated in the low-shear response, although its mechanism of action is currently unknown [ 33 , 34 , 36 ]. Several studies have mapped global transcriptomic responses of bacteria to the low-shear environment, comparing cells grown in spaceflight and clinostat conditions with corresponding ground controls [ 33 , 34 , 36 , 37 , 38 , 39 ], but to date, these studies have failed to yield insights into a detailed underlying molecular mechanism [ 40 , 41 ].…”
Section: Does a Microbial Analog Of Eukaryotic Mechanotransductionmentioning
confidence: 99%